Thoraco-lumbar high grade spinal cord astrocytoma: first documented case in a tertiary medical center and review of literature - Marquez, John Patrick R.; Mamba, Niccolo S. (International Journal of Research in Orthopaedics, 2020)
This presents the first documented case of high grade spinal cord astrocytoma in a pediatric patient treated at a tertiary medical center and gives a comprehensive review of literature on the most current modes of diagnosis, treatment, and prognosis. We report the case of a 7-year-old male with complaints of inability to ambulate and associated low back pain, which rapidly deteriorated to complete paraplegia. Magnetic resonance imaging (MRI) of his spine revealed an intradural intramedullary spinal cord lesion extending from T11 to L5 vertebra, with considerations of spinal astrocytoma and ependymoma. The patient underwent en bloc laminectomy on T9-L3, partial resection of the intramedullary cord tumor, and subsequent laminoplasty with mini plates and screws. Histopathologic studies showed spinal cord astrocytoma, World Health Organization (WHO) grade 3 (anaplastic type). The patient’s neurologic status did not improve after the surgery and was advised to undergo chemo-radiation therapy but was lost to follow up. Ten months post-operation, patient sought consult due to severe back pain, generalized body weakness, and difficulty of breathing and was then admitted. Patient’s condition worsened that eventually resulted to his demise.